Psychometric Properties of the Breast Cancer Screening Beliefs Questionnaire Among Women of Indian Ethnicity Living in Australia. Issue 4 (July 2016) - Kwok, Cannas; Pillay, Rona; Lee, Chun Fan
Abstract : Background: Indian women have been consistently reported as having low participation in breast cancer screening practices. A valid and reliable instrument to explore their breast cancer beliefs is essential for development of interventions to promote breast cancer screening practices. Objective: The aim of this study was to report the psychometric properties of the Breast Cancer Screening Beliefs Questionnaire (BCSBQ) in an Indian community in Australia. Methods: A convenience sample of 242 Indian Australian women was recruited from Indian community organizations and personal networking. Explanatory factor analysis was conducted to study the factor structure. Clinical validity was examined by Cuzick's nonparametric test, and Cronbach's α was used to assess internal consistency reliability. Results: Exploratory factor analysis showed a similar fit to the hypothesized 3-factor structure. The frequency of breast cancer screening practices was significantly associated with attitudes toward general health check-up. Knowledge and perceptions about the breast cancer scale were not significantly associated with clinical breast examinations and mammography. Perceived barriers to mammography were much less evident among women who engaged in breast awareness and clinical breast examination. Results indicated that the BCSBQ had satisfactory validity and internal consistency. Cronbach's α of the 3 subscales ranged from .81 to .91. Conclusions: The BCSBQ is a culturally appropriate, valid, and reliable instrument for assessing the beliefs, knowledge, and attitudes about breast cancer and breast cancer screening practices among women of Indian ethnic extraction living in Australia. Implication for Practice: The BCSBQ can be used to provide nurses with information relevant for the development of culturally sensitive breast health education programs.